Penerapan model problem based learning berbasis kearifan lokal untuk meningkatkan keterampilan berpikir kritis - Intan Budiarti; Gamaliel Septian Airlanda (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to improve critical thinking skills through the application of a Problem Based Learning based on local wisdom. This research is a classroom action research conducted in two cycles with planning, implementation, observation, and reflection stages. Data collection instruments use question instruments, observation sheets, documentation, and field notes. The subject of the study was the fourth grade students of SDN Salatiga 02. The results showed an increase in critical thinking skills as indicated by the data in the pre cycle of 41%, in the first cycle increased by 68.18%, and in the second cycle increased by 81.81%. Increasing critical thinking skills also affects the students learning outcomes. This is indicated by the learning outcomes on Indonesian language in pre cycle, cycle I, and cycle II, are 41%, 68%, and 86%. Furthermore, the learning outcomes of IPS in pre cycle, cycle I, and cycle II are 25%, 68%, and 86%.